Effect of infused lemon water (citrus limon) on Newborn Baby Weight (BBL) in pregnant rats (rattus norvegicus) exposed to electric cigarette vapor - Fadilah, Rahmawati Nurul; Nurdiana, Nurdiana; Mastuti, Ni Luh Putu Herli (Science Midwifery, 2024)
The electric cigarettes are said safe for health, in fact there are toxic substances, carcinogens, and unstable nicotine, it is suspected to cause low birth weight in pregnant women who are exposed to electric cigarette. Nicotine in electric cigarette is free radicals, so to ward off free radicals is required antioxidant. Infused lemon contains antioxidants that are higher than lime and are believed to resist free radicals from electric cigarettes. The purpose of research to determine the influence of infused lemon water in preventing low birth weight in pregnant rats (Rattus novergicus) exposed by electric cigarettes. The study used 30 pregnant rats, divided into 5 groups; Negative control (KN), positive control (KP), Treatment (P1), Treatment (P2), Treatment (P3). Using electric cigarette liquid 9 mg, and the difference in the weight of lemon in the making of infused water (P (1): 25g, P (2): 50g, P (3): 100g lemon + 100ml water). The treatment is given on day 1 ovulation to day 18, sacrificed on the 19th day ovulation then calculated the average weight of the baby. The average weight baby KN: 5.502g, KP: 2.821g, P (1): 4.301g, P (2): 4.888g, P (3): 5.435g. The result of One-way ANOVA indicates there is a significant difference in the treatment group with the value P=0,000 (P<0.05). The KP group differs significantly from KN. Group P (1,2,3) is significantly different from KP. The KN group is significantly different from P (1), but does not differ significantly from P (2, 3). The group P (1) differs significantly with P (3). Infused lemon juice can prevent the occurrence of low birth weight in the child of the pregnant rats that’s exposed by electric cigarettes especially in group P (3).